GUEST EDITORIAL - Adendorff, Susan (The South African Journal of Industrial Engineering, 2016)
“All we know about the new economic world tells us that nations which train engineers will prevail over those which train lawyers. No nation has ever sued its way to greatness.” - ― Richard Douglas Lamm (1935 - ) (politician, writer, public accountant, lawyer) Industrial Engineering was introduced to the South African higher education market in 1961 at the University of Pretoria and thus 2016 marks the 55th year of Industrial Engineering in South Africa. The feature article in this edition of the South African Journal of Industrial Engineering provides a comprehensive overview of the steady growth of the discipline in South Africa. It also illustrates the fact that Industrial Engineering as a discipline has matured to the point where employment of IE’s occurs in various industries from industrial (manufacturing) to services. However, complacency about the current role of IE’s in the South African economy should be avoided since the research supporting the article indicates that the potential for IE’s in numerous other industries exists and hence these industries should be targeted as potential employers of industrial engineers. The question that begs answering is who should fulfil this role of expanding the awareness of the potential role for industrial engineers. The article indicates that more higher education institutions have introduced industrial engineering as a discipline in recent times. Is it the sole responsibility of these higher education institutions to create awareness in industry since this will lead to more job opportunities for their graduates? Or should this responsibility reside with the sponsor of this journal, the Southern African Institute for Industrial Engineering in its role as the custodian of the discipline not only in South Africa, but in the Southern African region? The fact of the matter is that IE’s can contribute significantly in times of economic hardship as currently experienced in South Africa – low or non-existent economic growth will only change if productivity levels are improved through concerted optimisation efforts. Furthermore, as stated in the feature article, very few IE’s are employed in government. Given the current outcry regarding poor service delivery by government (central and local), a concerted effort should be made to create awareness about the role of IE’s at this level. A recent survey by CareerJunction put South African industrial engineers in the top ten careers in terms of salaries. This attests to the fact that where industrial engineers are employed, their contribution is seen as valuable and the salaries employers are willing to pay for their services confirms this fact. The feature article proposes a working group to address issues of representivity in the South African IE community – however, a working group on promoting the profession is also needed. As opposed to other disciplines, the contributions of IE’s are often less tangible than those of the other disciplines (eg civil engineering) and hence require a special effort in creating awareness. Susan Adendorff Honorary Fellow SAIIE